2001
DOI: 10.3354/meps212283
|View full text |Cite
|
Sign up to set email alerts
|

Albatross response to survey vessels: implications for studies of the distribution, abundance, and prey consumption of seabird populations

Abstract: The study of marine bird ecology at sea is complicated by the tendency of many species to follow and otherwise attend vessels. Vessel-attraction likely biases abundance estimates and blurs the correlation between seabird distributions and habitat features over scales of tens of kilometers. Moreover, ship-following behavior inhibits the statistical analysis of seabird distributions because samples too closely spaced in time and space are not independent. These biases have important implications when estimating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…(2) The largest fulmar colonies host considerably more birds than the colony catalog suggests. Hyrenbach (2001) reported that ship-based surveys overestimate albatross densities off California by a factor of 4. While observers in our study were instructed not to count obviously ship-following birds, there is no known antidote against ship-attraction.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The largest fulmar colonies host considerably more birds than the colony catalog suggests. Hyrenbach (2001) reported that ship-based surveys overestimate albatross densities off California by a factor of 4. While observers in our study were instructed not to count obviously ship-following birds, there is no known antidote against ship-attraction.…”
Section: Discussionmentioning
confidence: 99%
“…A common problem in ecological research is the difficulty of estimating prey consumption by a predator population in a spatial context, and this often limits a satisfactory understanding of trophodynamics in even simple ecosystems (Hyrenbach 2001 . Histogram of linear discriminant scores derived from prey data by separating prey into two groups: fishes (grey bars) and squid (black bars).…”
Section: Discussionmentioning
confidence: 99%
“…Part of this process requires information on both the spatial and the temporal aspects of predator diet (Brown et al 1999;Shurin 2001), and this is particularly important for wide-ranging species that occupy vastly different ecological zones during the course of their regular movements (Hyrenbach 2001). In the case of wideranging top-level marine predators, such as whales, seals and seabirds, there is scant information on diet structure with respect to individual, geographical and temporal variation (Iverson et al 1997b;Hindell et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These observations, however, have been constrained by the tendency of albatrosses to follow survey vessels, and by the inability of observers to determine the origin, gender, and reproductive status of birds sighted at sea , Hyrenbach 2001.…”
Section: Introductionmentioning
confidence: 99%